Livelihood assets’ influence on Ugandan farmers’ control practices for Banana Xanthomonas Wilt (BXW) - Pagnani, Tiziana; Gotor, Elisabetta; Kikulwe, Enoch Mutebi; Caracciolo, Francesco (Springer, 2021)
This study analyzes the influence of livelihood assets on Ugandan farmers’ decisions to control Banana Xanthomonas Wilt (BXW), a disease that has threatened banana production and the livelihoods of Ugandan farmers since 2001. The BXW control strategy is based on the simultaneous implementation of four cultural practices: de-budding, infected plant removal, disinfecting tools, and using clean planting materials. The Sustainable Rural Livelihood (SRL) framework represents a very useful theoretical architecture for examining the interplay between livelihood systems of rural Ugandan households and the external context. Empirically, this study applies a double-hurdle model with the base assumption that the two adoption decision processes (whether to adopt and the intensity of adoption of the cultural practices) are separate. Results indicate that the vulnerability context and the human, social, natural, and physical capitals are the factors that drive farmers to adopt the identified strategy. Farmers’ decisions about the extent of adoption are instead negatively influenced by natural capital and positively associated with social capital. These findings highlight the importance of supporting the improvement of livelihood assets to enable tailored support to farmers. It is particularly important to support the social and natural capitals that facilitate information exchange and provide critical resources for the adoption of the BXW control strategy.